Fuente Álamo. Vorbericht über die Grabung 1999 in der bronzezeitlichen Höhensiedlung - Pingel, Volker; Schubart, Hermanfrid; Arteaga Matute, Oswaldo; Roos, Anna-Maria; Kunst, Michael (Madrider Mitteilungen, 2020)
Deutsche Zusammenfassung folgt.